Finite superstrings - Taylor, J. G. 1931- (World Scientific Pub. Co., 1992)
This is the first complete account of the construction and finiteness analysis of multi-loop scattering amplitudes for superstrings, and of the guarantee that for certain superstrings (in particular the heterotic one), the symmetries of the theory in the embedding space-time are those of the super-Poincaré group SP10 and that the multi-loop amplitudes are each finite. The book attempts to be self-contained in its analysis, although it draws on the works of many researchers. It also presents the first complete field theory for such superstrings. As such it demonstrates that gravity can be quantized satisfactorily by superstrings